It's now or nether! - Huett, Caleb Zane (Huett, Caleb Zane. Minecraft Ironsword Academy, 2025)
"Eek journeys into the nether alone, and Ash has to go after him. Piglins and hoglins at every turn make survival seem unlikely! Meanwhile, Po, Harper, and their fellow students at Ironsword Academy get into deep trouble with Principal Ferris when they wage a friendly sword fight in the cafeteria. Now they will have to spend the afternoon doing chores around the school instead of playing Minecraft. Will they get done in time to save Ash and Eek?"--Back cover.